Analisa Tingkat Resiko Tata Kelola Teknologi Informasi Perguruan Tinggi Menggunakan Model Framework National Institute of Standards & Technology (NIST) Special Publication 800-30 dan IT General Control Questionnaire (ITGCQ) - Susilo Susilo (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2017)
Information and Communication Technology (ICT) Governance is strongly associated with the successful of an organization's management especially about how to control physical assets, data and information were applied. In organizations, universities (Higher Education) Data and information is extremely important given the orientation of utilization is in the form of shared knowledge, through teaching and learning, research and community service (Tri Dharma). With a potential source of threats posed by humans (Human Threats), natural disasters (Natural Threats), and disruption of the environment (Environmental Threats) can interfere with the management of ICT colleges. NIST Framework Model is implemented by integrating the concept of Information Technology (IT) Risk Management through assessment risk mitigation strategies and recommendations to measure the probability of the threat and the level of impact on the institution. Then, through indepth interviews with ICT department/unit using IT General Control Questionnaire (ITGCQ) and also review operational documents to found risk analysis issues. Risk analysis results are summarized in the form of safeguard implementation plan to reduce the level of IT risk governance PTS. XYZ. More and more ICT management activities that do not have control, the higher the level of risk management of ICT.